2011
DOI: 10.1007/s00198-011-1575-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fracture in elderly men: a population-based prospective study

Abstract: These results underline the importance of assessment of dizziness, falls and those with a family history of hip fracture. Frequent urination and erectile dysfunction were independently associated with increased fracture risk. Although the mechanism of association is unknown, these variables are likely to be indicators of frailty or hypogonadism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…For the elderly, the most powerful risk factor of fracture is age [34]. In our study, the previous 5 months of each patient became the control group, and the age distribution of the patient group and control group is identical.…”
Section: Discussionmentioning
confidence: 94%
“…For the elderly, the most powerful risk factor of fracture is age [34]. In our study, the previous 5 months of each patient became the control group, and the age distribution of the patient group and control group is identical.…”
Section: Discussionmentioning
confidence: 94%
“…This study identified predictive factors for osteoporotic fractures in elderly men that were not collected in our study, including quadriceps strength and sway factor (a measure of postural stability). Another known risk factor for fractures missing from our dataset was family history of fractures .…”
Section: Discussionmentioning
confidence: 99%
“…40 This review, published in 2016, included 6 retrospective and 3 prospective studies, and all the prospective studies but not the retrospective ones were also included in our review. 31,37,38 The prior review did not include 6 studies that proved eligible in our systematic review, namely 2 conducted among men (1 full text article 36 and 1 conference abstract 29 ), 2 conducted among both genders that were reported before the publication of their review, 32,33 and 2 (both conducted among men) that were published after their review appeared. 34,39 The prior review did not conduct a meta-analysis, nor did the authors provide estimates of the impact of nocturia on the absolute risks of falls or fractures, or assess the quality of evidence.…”
Section: Relation To Prior Workmentioning
confidence: 99%